2004
DOI: 10.1023/b:jopc.0000039554.18157.69
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Biochemical Characterization of Asclepain c I from the Latex of Asclepias curassavica L.

Abstract: In this work we report the isolation, purification and characterization of a new protease from latex of Asclepias curassavica L. Crude extract (CE) was obtained by gathering latex on 0.1 M citric-phosphate buffer with EDTA and cysteine with subsequent ultracentrifugation. Proteolytic assays were made on casein or azocasein as substrates. Caseinolytic activity was completely inhibited by E-64. Stability at different temperatures, optimum pH and ionic strength were evaluated by measuring the residual caseinolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 35 publications
2
30
0
5
Order By: Relevance
“…Hence, there are only minor but noticeable differences in the specificity of recBM and cBM to the substrates. The data obtained in this study is comparable to the kinetic data reported for cysteine proteases including stem bromelain [20,24] granulosain [21], ascepalin [25], hieronymain II [26] and penduliforain I [27]. Based on kinetic data obtained in this study, it can be inferred that the kinetic behavior of recBM (containing His 6x tag, signal and propeptide) is not much different to that of mature cBM.…”
Section: Kinetic Parameters Estimationssupporting
confidence: 87%
“…Hence, there are only minor but noticeable differences in the specificity of recBM and cBM to the substrates. The data obtained in this study is comparable to the kinetic data reported for cysteine proteases including stem bromelain [20,24] granulosain [21], ascepalin [25], hieronymain II [26] and penduliforain I [27]. Based on kinetic data obtained in this study, it can be inferred that the kinetic behavior of recBM (containing His 6x tag, signal and propeptide) is not much different to that of mature cBM.…”
Section: Kinetic Parameters Estimationssupporting
confidence: 87%
“…Other peptidases of the Apocynaceae family display different substrate specificity. Asclepain cII and asclepain cI from latex of A. curassavica strongly prefer Asp and Tyr derivatives (Liggieri et al 2004. Morrenain bI exhibits strong preference for Ala and Asp derivatives while morrenain bII prefers Asp and Gly, both enzymes isolated from latex of Morrenia brachystephana (VairoCavalli et al 2001(VairoCavalli et al , 2003.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of pH on enzyme activity of the purified protease was measured with casein (pH range 6.4-10.5) using 10 mM sodium salts of the following ''Good'' buffers: MES, MOPS, TAPS, AMPSO and CAPS (Liggieri et al 2004). …”
Section: Protein Purificationmentioning
confidence: 99%
“…Moreover, plant latices are described as rich in small secondary metabolites, non-protein amino acids, enzymatic and non-enzymatic proteins in their serum phase (Yeang et al 2002;Taira et al 2005). Recently, a vast number of cysteine proteases have been described as occurring in many latex-producing plants (Liggieri et al 2004;Morcelle et al 2004a, b). Chitinases, lectins, lipases, oxidative and other hydrolytic enzymes have also been described as occurring in latex fluids (Stirpe et al 1993;Azarkan et al 1997;Giordani et al 1992;Amani et al 2007;Fiorillo et al 2007).…”
Section: Introductionmentioning
confidence: 99%